ADDICTION TO MOBILE GAMES AND DISTURBANCE OF SLEEP RHYTHMS (Innovate Conferences, 2025)
This article provides an in-depth analysis of the impact of mobile game addiction on the rhythms of sleep hormones-particularly melatonin and cortisol-among young people. Based on scientific sources, the study highlights alterations in the secretion patterns of these hormones resulting from prolonged and nighttime engagement with mobile games, as well as their effects on health. Research indicates that in individuals addicted to mobile games, melatonin levels are on average 3540% lower than normal, while the circadian rhythm of cortisol is delayed by 23 hours. Consequently, screen-induced eye strain, sleep deprivation, chronic fatigue, irritability, and neurobiological dysfunctions in brain activity are observed. Therefore, it is recommended to strengthen preventive educational efforts among youth, promote sleep hygiene, reduce mobile game addiction, limit screen exposure during evening hours, engage in physical activity, and carefully use natural remedies that help restore biological rhythms.